Strategi Dakwah Di Era Digital (Studi Kasus pada Ma’had Al-Jami’ah UIN Sumatera Utara Medan) - Aulia Nur; Nashrillah MG (Dinasti Research, 2024)
The aim of this research is to determine the Da'wah Strategy in the Digital Era, specifically focusing on the case of Ma'had Al-Jami'ah UIN SU. This research method uses a qualitative approach which focuses on providing a detailed description of the subject matter. Data collection methods include the use of observation, interviews, and documentation practices. Based on research findings, analysis and interpretation, taking into account various ideas, the following conclusion can be drawn: the da'wah strategy in the digital era (case study at Ma'had Al-Jami'ah UIN SU) is to improve the da'wah skills of students in the digital era , the use of social media in the digital era and improving the language skills of students in the digital era. Through the implementation of activities carried out by Ma'had Al-Jami'ah UIN SU, namely celebrating the Ma'had Al-Jami'ah UIN SU event, holding regular muhadharah for students, carrying out night and mudasah study activities, murottal Qur'an and creativity art